1985
DOI: 10.1038/313027a0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetics of Krüppel, a gene required for segmentation of the Drosophila embryo

Abstract: Krüppel is a member of the 'gap' class of segmentation genes of Drosophila melanogaster, mutations of which cause contiguous groups of segments of the fruitfly embryo to fail to develop. In the case of Krüppel mutant embryos, thoracic and anterior abdominal segments are deleted. The molecular cloning of the Krüppel locus will lead to an understanding of the crucial role that gap genes seem to have in early embryonic development. It has already allowed the identification of a blastoderm-specific Krüppel transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
97
0
1

Year Published

1985
1985
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 220 publications
(100 citation statements)
references
References 22 publications
2
97
0
1
Order By: Relevance
“…Further, to address the question of whether antisense RNA can inhibit genes transcribed in the cell nucleus, we injected antisense CAT RNA into the oocyte cytoplasm and then tested the expression of a plasmid DNA coding for CAT injected into the oocyte nucleus. Our data complement and support the findings of Melton who has independently obtained similar results using Xenopus globin mRNA (13), and the results of Preiss et al (16) who have shown that antisense RNA complementary to Kriipple mRNA can phenocopy a KrOpple mutation in Drosophila. …”
supporting
confidence: 82%
“…Further, to address the question of whether antisense RNA can inhibit genes transcribed in the cell nucleus, we injected antisense CAT RNA into the oocyte cytoplasm and then tested the expression of a plasmid DNA coding for CAT injected into the oocyte nucleus. Our data complement and support the findings of Melton who has independently obtained similar results using Xenopus globin mRNA (13), and the results of Preiss et al (16) who have shown that antisense RNA complementary to Kriipple mRNA can phenocopy a KrOpple mutation in Drosophila. …”
supporting
confidence: 82%
“…Furthermore, one copy of the FX(10.7)-Kr-2F transgene rescues the segmentation phenotype of homozygous Kr 1 lack-of-function mutant embryos, indicating that FLAG-tagged Krü ppel is func-tional (34,35) (Fig. 1, C-F).…”
Section: Generation Of a Flag-tagged Krü Ppel Protein And Itsmentioning
confidence: 99%
“…To solve this apparent dilemma and to thereby demonstrate that our screen has indeed led to Krü ppel target genes, we asked whether Krü ppel does regulate ken expression in vivo by performing in situ hybridizations of ken probes to whole mount preparations of wild type and homozygous Kr 1 lack-of-function mutant embryos (34,35). In wild type, Krü ppel is initially expressed in a broad band in the central region of the blastoderm (15).…”
Section: Figmentioning
confidence: 99%
“…The name "Krüppel" is derived from the Drosophila protein krüppel (meaning "cripple" in German), which shares homology of proteins to DNA-binding domains 5,6) . Krüppel-deficient embryos in Drosophila die with consequences of abnormal thoracic and abdominal segmentation and thus appeared "crippled."…”
Section: Introductionmentioning
confidence: 99%